Elemental and morphological characterization of a gemfibrozile tablet by the energy dispersive X-ray fluorescence technique - Bravo Cabrejos, Jorge Aurelio (2021)
Applying the analytical technique of energy dispersive X-ray fluorescence (EDXRF) the elemental composition of the film that coats gemfibrozil medicinal tablets has been determined. The respective EDXRF spectrum shows relatively intense characteristic K X-rays peaks of titanium about a hundred times more intense than the other X-ray peaks present in the spectrum. The quantitative analysis of this spectrum, based on the assumption that the material within the tablet in uniformly distributed, shows that the calculated amplitude of the K$_{β}$ X-rays of titanium is about 25% larger than the recorded peak indicating that the titanium is distributed as a film. The literature gives reference to the application of titanium oxide for coating tablets. Based on this hypothesis the thickness of the TiO$_{2}$ oxide film is calculated to be 1.90 $μ$m.